2011
DOI: 10.1387/ijdb.113315el
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of histone deacetylase 1 and Notch signalling restrict expression of erm and fgf20a to hindbrain rhombomere centres during zebrafish neurogenesis

Abstract: The rate and pattern of neurogenesis in the developing vertebrate nervous system are controlled by a complex interplay of intercellular signalling pathways and transcriptional control mechanisms. In the zebrafish hindbrain, Fgf20a promotes transcription of the gene encoding the ETS-domain transcription factor Erm in the non-neurogenic centres of rhombomeres. Here, we demonstrate that the epigenetic regulator, Histone Deacetylase 1 (Hdac1) and the Notch signalling pathway have opposing functions in regulating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Wnt/β‐catenin signalling has been shown to play a role in regulating migration of PLL primordia, proliferation of lateral line progenitors during development, neuromast formation and hair cell regeneration . HDACs can participate in numerous developmental signalling pathways, including Notch and Wnt, by interacting with transcriptional repressors or activators to form transcriptional complexes . An earlier study found that HDAC1 antagonized Wnt signalling to promote cell cycle exit of retinoblasts .…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β‐catenin signalling has been shown to play a role in regulating migration of PLL primordia, proliferation of lateral line progenitors during development, neuromast formation and hair cell regeneration . HDACs can participate in numerous developmental signalling pathways, including Notch and Wnt, by interacting with transcriptional repressors or activators to form transcriptional complexes . An earlier study found that HDAC1 antagonized Wnt signalling to promote cell cycle exit of retinoblasts .…”
Section: Discussionmentioning
confidence: 99%
“…The morpholino against hdac1 (5′-TTGTTCCTTGAGAACTCAGCGCCAT-3′) was targeted to the translational initiation site, as ref. 19 . The scramble morpholino sequences was: 5′-CCTCTTACCTCAGTTACAATTTATA-3′.…”
Section: Methodsmentioning
confidence: 99%
“…In zebrafish, Hdac1 is specifically required to promote neuronal specification in the developing Central Nervous System (CNS) 18 19 20 21 . Hdac1 is also needed for the switch from proliferation to differentiation in the zebrafish retina and optic stalk.…”
mentioning
confidence: 99%
“…Other studies have shown that HDAC1 mutant zebrafish as well as those treated with antimorpholino oligo against HDAC1 exhibited impaired neurogenesis in the hindbrain (Cunliffe, 2004;Harrison et al, 2011;Lightman et al, 2011;Jacob et al, 2014) and retina (Yamaguchi et al, 2005). Studies have also revealed that HDAC1 promotes the transformation of neural progenitors into differentiated neurons and glia (Cunliffe, 2004;Yamaguchi et al, 2005;Harrison et al, 2011;Lightman et al, 2011;Jacob et al, 2014). Mice lacking HDAC1 and HDAC2 have exhibited impaired migration of neural precursors during brain development (Montgomery et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the retina of HDAC1 mutant zebrafish, Yamaguchi et al (2005) showed that HDAC1 antagonizes Notch as well as Wnt pathways to promote cell-cycle exit and subsequent inhibited neurogenesis in the zebrafish retina. HDAC1 has also been shown to be necessary for the repression of Notch target gene expression in the hindbrain of embryonic zebrafish (Cunliffe, 2004;Harrison et al, 2011;Lightman et al, 2011;Jacob et al, 2014).…”
Section: Introductionmentioning
confidence: 99%